2023
DOI: 10.21203/rs.3.rs-2303336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the Causal Relationship Between Glomerular Filtration Rate and Cardiovascular Disease: A Mendelian Randomization Study

Abstract: BACKGROUND A large number of observational studies have now shown that a decrease in the estimated glomerular filtration rate (eGFR) is associated with an increased risk of cardiovascular disease. However, there are no uniform conclusions regarding the potential relationship between the estimated glomerular filtration rate and cardiovascular disease. We will explore the causal relationship between estimated glomerular filtration rate and cardiovascular disease for the first time using a two-sample Mendelian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several earlier studies employed MR to look into the connection between air pollution and different health outcomes. [19][20][21][22][23][24][25][26][27][28][29][30][31] Yi et al, for example, conducted a TSMR analysis reporting a causal link between air pollution and neurodegenerative disorders (Alzheimer's disease and Parkinson's diseases). 24 Wang et al demonstrated the causal evidence that air pollution might cause multiple cancer types by MR. 20 However, the causal relationship and underlying biological mechanisms between air pollution and ALS remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies employed MR to look into the connection between air pollution and different health outcomes. [19][20][21][22][23][24][25][26][27][28][29][30][31] Yi et al, for example, conducted a TSMR analysis reporting a causal link between air pollution and neurodegenerative disorders (Alzheimer's disease and Parkinson's diseases). 24 Wang et al demonstrated the causal evidence that air pollution might cause multiple cancer types by MR. 20 However, the causal relationship and underlying biological mechanisms between air pollution and ALS remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%